2007
DOI: 10.1111/j.1469-7998.2006.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with your food: geckos in termitaria of Cantão

Abstract: We tested three non-exclusive hypotheses that the lizard, Gymnodactylus carvalhoi, lives in termitaria to avoid thermal extremes, to avoid predators, or because of an abundance of food (dietary specialist). We first confirm that these geckos are restricted to termitaria in the region studied. Body temperatures (T b ) of geckos averaged below environmental temperatures during day outside of termitaria and above outside temperatures at night; T b averaged only slightly higher than temperatures inside termitaria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…In contrast, the largely arboreal Chlamydosaurus kingii (Agamidae) escapes fires by climbing to treetops or by sheltering in hollow tree trunks and termitaria (Braithwaite, 1987;Griffiths and Christian, 1996;Andersen et al, 2005). Termites are highly diverse and abundant in the Cerrado, providing food and shelter for many lizard species Vitt et al, 2007b;Costa et al, 2008). Large logs may also serve as barriers against low intensity fires in forest habitats; humid leaf litter that accumulates below logs may shelter small animals (Andrew et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the largely arboreal Chlamydosaurus kingii (Agamidae) escapes fires by climbing to treetops or by sheltering in hollow tree trunks and termitaria (Braithwaite, 1987;Griffiths and Christian, 1996;Andersen et al, 2005). Termites are highly diverse and abundant in the Cerrado, providing food and shelter for many lizard species Vitt et al, 2007b;Costa et al, 2008). Large logs may also serve as barriers against low intensity fires in forest habitats; humid leaf litter that accumulates below logs may shelter small animals (Andrew et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found a positive association between lizard richness and termites in savanna-like environments (Morton & James 1988, Costa et al 2008). Nests offer favorable microhabitats for oviposition (Vitt et al 2007a, Knapp & Owens 2008, thermal requirements (Vitt et al 2007b), and shelter (Vitt & Caldwell 1993), and can influence distributions at the microhabitat scale (Vitt et al 2007a). Nests offer favorable microhabitats for oviposition (Vitt et al 2007a, Knapp & Owens 2008, thermal requirements (Vitt et al 2007b), and shelter (Vitt & Caldwell 1993), and can influence distributions at the microhabitat scale (Vitt et al 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…We could therefore tentatively assume that these specimens are fertile and that the chromosomal polymorphism is fixed in the population from the UHE Serra da Mesa. These lizards are territorial with activities either restricted to the interior or the surroundings of termite mounds, where they live in small groups and are especially abundant, or under rocks or fallen trunks [Colli et al, 2003;Vitt et al, 2007]. Thus, it is possible that their population structure may explain the origin, distribution and maintenance of this variation.…”
Section: Discussionmentioning
confidence: 99%